Endocrine and physiological responses of hatchling American kestrels (Falco sparverius) following embryonic exposure to technical short-chain chlorinated paraffins (C10-13). (December 2020) - Fernie, K.J.; Karouna-Renier, N.K.; Letcher, R.J.; Schultz, S.L.; Peters, L.E.; Palace, V.; Henry, P.F.P.
Graphical abstract: Highlights: Captive kestrels exposed in ovo to SCCP concentrations found in wild birds. Sex-specific differences in SCCP uptake/deposition and thyroid effects at hatching. SCCP reduced thyroid hormones, altered thyroid gland function but not deiodinases. Thyroidal changes correlated with hatchling size and smaller immune organs. Effects in captive kestrels warrant future research in wild birds. Abstract: Short chain chlorinated paraffins (SCCPs) are complex mixtures of polychlorinated n -alkanes, shown to bioaccumulate but with unknown effects in wild birds. The present study examined development-related effects of SCCPs on captive American kestrels ( Falco sparverius ) treated in ovo on embryonic day (ED) 5 by injection with technical Chloroparaffin® (C10-13, 55.5% Cl) at environmentally relevant nominal (measured) concentrations of 10 (10), 50 (29) or 100 (97) ng ΣSCCP/g egg ww, and artificially incubated until hatching (ED27–ED29). The SCCP concentrations measured in the yolk sacs of the hatchling kestrels bracketed concentrations reported in the eggs of wild birds. Uptake and deposition of these SCCPs differed between male and female hatchlings, with only males showing differences in SCCP concentrations, being highest in the high-dose males than each of the other male groups. Embryonic exposure to SCCPs suppressed glandular total thyroxine (TT4) (20–33%) and reduced circulating triiodothyronine (TT3) (37–40%) in male hatchlings only when compared to control males, but had no effect on glandular TT3 or circulating TT4 in male or female kestrels. Histological assessments of thyroid glands showed that both sexes experienced significant structural changes indicative of gland activation. These thyroid glandular changes and the variations in SCCP concentrations were related to circulating TT3 in female hatchlings. Hepatic deiodinase enzyme (D1, D2) activities were stable and no SCCP-related changes were observed in hatching success, hatchling size, or immune organ size. However, several of the thyroid function indicators were correlated with hatchling size and smaller bursas and spleens, possibly indirectly through SCCP-induced changes in thyroid function. Because changes in thyroid function were evident at concentrations measured in wild bird eggs, similar changes may occur in wild nestlings. The potential impact of these changes on thyroid-mediated growth and survival in wild birds requires further investigation.